2015
DOI: 10.7127/rbai.v9n400356
|View full text |Cite
|
Sign up to set email alerts
|

DETERMINAÇÃO DO ÍNDICE DE ESTRESSE HÍDRICO EM TOMATEIROS CEREJA ( Lycopersicum Solanum var. cerasiforme.) COM CÂMARA INFRAVERMELHA

Abstract: Infrared thermometry is a possibility of detection of plant water stress by measuring the temperature of a portion of the canopy without requiring physical contact with the sheets. The purpose of this study was determining the crop water stress index in tomato cherry using the leaf temperature in plants as an indicator of water stress. Plants were grown in a greenhouse situated in the Department of Biosystems Engineering at the Escola Superior de Agricultura "Luiz de Queiroz "in Piracicaba, São Paulo. The plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 10 publications
2
6
0
7
Order By: Relevance
“…This result corroborates with those found by López et al (2009b) with husk tomato in Mexico, Ghaemi et al (2015) with eggplant in Iran, Ramírez et al (2015) with cherry tomato in Piracicaba-SP, and also those found by Erdem et where: r a -aerodynamic resistance, s m -1 ; γ -psychrometric constant, kPa ºC -1 ; R n -net radiation balance, W m -2 ; G -heat flux in the soil = zero; ρ ar -air density at constant pressure, kg m -3 ; Cp -air specific heat at constant pressure, J kg -1 ºC -1 = 1013; ∆ -slope of the saturation water vapor pressure curve at the temperature, kPa ºC -1 ; and, VPD -vapor pressure deficit, kPa.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…This result corroborates with those found by López et al (2009b) with husk tomato in Mexico, Ghaemi et al (2015) with eggplant in Iran, Ramírez et al (2015) with cherry tomato in Piracicaba-SP, and also those found by Erdem et where: r a -aerodynamic resistance, s m -1 ; γ -psychrometric constant, kPa ºC -1 ; R n -net radiation balance, W m -2 ; G -heat flux in the soil = zero; ρ ar -air density at constant pressure, kg m -3 ; Cp -air specific heat at constant pressure, J kg -1 ºC -1 = 1013; ∆ -slope of the saturation water vapor pressure curve at the temperature, kPa ºC -1 ; and, VPD -vapor pressure deficit, kPa.…”
Section: Resultssupporting
confidence: 83%
“…Fast and accurate assessment of plant water status is very useful in irrigation management, especially in crops such as industrial tomato (Solanum lycopersicom L.), which is highly sensitive to water stress (Ramírez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O parâmetro Crop Water Stress Index (CWSI), determinado através da temperatura foliar, pode ser uma alternativa para obtenção do estado hídrico das plantas e este tem sido estudado em diversas culturas como cana-de-açúcar (TRENTIN, 2010), citrus (ZARCO-TEJADA; GONZÁLEZ-DUGO; BERNI, 2012), uva (BELLVERT et al, 2014), oliveira (BERNI et al, 2009), algodão (COHEN et al, 2014, tomate (RAMÍREZ et al, 2015a) …”
Section: Standards Of Thermal Response To Drought In Irrigated Coffeeunclassified
“…A partir desses valores é possível afirmar que nas condições do experimento, a temperatura foliar, medida com a câmera térmica, das plantas submetidas a lâminas deficitárias foi aproximadamente 1,0 ºC maior que a temperatura foliar das plantas que receberam os tratamentos L130% e L100%. Ramírez et al (2015a) …”
Section: Fração De Radiação Fotossinteticamente Ativaunclassified